Application of de novo programming method in production planning at UMKM seasoning Opaque Tuntungan II - Damanik, Mahyuni Br; Aprilia, Rima (Universitas Islam Negeri Raden Intan Lampung, 2024)
Optimization is a way of solving mathematical problems to get optimal results. One way to solve optimization problems is to use a linear program. One of the developments of linear program models that can be used in optimization problems is de novo programming. This research uses de novo programming to maximize profits at UMKM Seasoning Opaque. Based on the results of the analysis with the POM-QM application, it can be concluded that the production of Tuntungan II seasoning opaque factory for 7 weeks is optimal with the production of 2,031 kg of salted seasoning opaque, 1,170 kg of regular spicy seasoning opaque, and 3,381 kg of round spicy seasoning opaque. Using the De Novo Programming method, it was found that the optimal production for 7 weeks of the opaque spice factory in Tuntungan II for 7 weeks had a profit of Rp12,317,240.